More bark than bytes? Reflections on 21+ years of geocomputation. Issue 4 (July 2017) - Harris, Richard; O'Sullivan, David; Gahegan, Mark; Charlton, Martin; Comber, Lex; Longley, Paul; Brunsdon, Chris; Malleson, Nick; Heppenstall, Alison; Singleton, Alex; Arribas-Bel, Daniel; Evans, Andy
This year marks the 21st anniversary of the International GeoComputation Conference Series. To celebrate the occasion, Environment and Planning B invited some members of the geocomputational community to reflect on its achievements, some of the unrealised potential, and to identify some of the on-going challenges.